Renal biopsy outcomes in patients with unexplained rise in serum creatinine - Wan Ali, Wan Ahmad Syahril Rozli; Chee, Eng Chan; Mohamad Nor, Fariz Safhan; Mat Nor, Khadijah (Science Direct, 2017)
Introduction: Renal biopsy is an invasive but necessary procedure to determine the exact diagnosis of patients, especially in patients with an unexplained renal impairment. The histopathological examination is vital not only for diagnosis, but also to prognosticate patients’ condition. Objective: This study was aimed at evaluating the results of renal bi- opsy in patients with unexplained rise in serum creatinine, and its association with the patients’ clinical characteristics. Methodology: This was a retrospective study done with data collected from biopsy results in Hospital Tg Ampuan Afzan, Kuantan between 2016 until April 2017. Baseline demographics, risk factors, rate and duration of worsening serum creatinine and the biopsy results were recorded. Results: There were 21 patients in which 14 (66.6%) were males, and 7 (33.3%) of the patients were females. The median age of the patients were 32.0 (IQR 21.0) years. A total of 15 (71.4%) patients have got no other disease comorbidities, and 5 (23.8%) were di- abetics. Three (14.2%) patients have history of taking herbal supplements. The median duration of deranged creatinine was 14.0 (IQR 13.0) days. The median urea on presentation was 10.0 (IQR 11.1) mmol/L, and the median Creatinine was 306.0 ( IQR 324.0) mmol/L. The median rise in creatinine was 137.0 (IQR 182.0) mmol/ L. Biopsy complications which were perinephric collection were noted in two patients (9.5%). The median glomeruli number attained was 20 (IQR 16). Mesangial matrix expansion and hyper- cellularity was noted in 12 (57.0%) patients. Tubular atrophy and interstitial inflammation was present in 17 (80.9%) patients. Out of the 21 biopsies, 13 (61.9%) were diagnosed to have glomerulone- phritis. Within that group, two (9.5%) of the patients were diag- nosed with Crescentic Lupus Nephritis Class IV. Other glomerulonephritis included IgA Nephropathy in 2 patients (9.5%) and Minimal change GN (9.5%). Eight (38.1%) of the results showed hypertensive changes (14.3%), Diabetic changes (4.3%), focal global glomerulosclerosis (4.3%) and Thrombotic micro- angiopathy (4.3%). The creatinine on presentation and also inter- stitial inflammation and tubular atrophy is not significantly correlated with the glomerulosclerosis group. Conclusion: Renal biopsy definitely still plays the most vital and irre- placeable role in the investigation of cases with unexplained renal impairment. Despite a vastly variable biopsy results between patients, renal biopsy has helped in determining the best treatment and prog- nosis for the patients in our study.